Role of politically motivated internet addiction and ideological passion in linking college student's mental health education and wellbeing - Meng, Shuyu (Frontiers in Psychiatry, 2022)
There has been an ever-rising concern for psychological well-being and its role in hindering or causing the college student’s ability to learn across world. Therefore, the role of societal health awareness has emerged as a topic of interest in managing the issue of college students’ well-being in term of societal effects. This study intends to look into the relationship between mental health education and psychological well-being, along with the moderating role of politically motivated internet addiction and the ideological passion of Chinese college students by considering the UN-SDGs. For the given reason, the random sampling method was employed for collecting data from target respondents. The study uses 750 questionnaires prepared on a five-point Likert scale that were distributed to the respondents with an expected response rate of 50%. The partial least square (PLS) software was used to analyze the data for this study. The study concludes that there is a significant moderating role of politically motivated internet addiction and ideological passion in the relationship between college students’ mental health and well-being under SDGs. Study meaningfully contributes to the body of knowledge, by establishing the tentative relationships, between the above-stated variables, in pursuit of improving the psychological well-being of college students through mental health education and awareness policies and SDGs implications for welfare of students.